Consumers' choice-blindness to ingredient information. (1st November 2016) - Cheung, T.T.L.; Junghans, A.F.; Dijksterhuis, G.B.; Kroese, F.; Johansson, P.; Hall, L.; De Ridder, D.T.D.
Abstract: Food manufacturers and policy makers have been tailoring food product ingredient information to consumers' self-reported preference for natural products and concerns over food additives. Yet, the influence of this ingredient information on consumers remains inconclusive. The current study aimed at examining the first step in such influence, which is consumers' attention to ingredient information on food product packaging. Employing the choice-blindness paradigm, the current study assessed whether participants would detect a covertly made change to the naturalness of ingredient list throughout a product evaluation procedure. Results revealed that only few consumers detected the change on the ingredient lists. Detection was improved when consumers were instructed to judge the naturalness of the product as compared to evaluating the product in general. These findings challenge consumers' self-reported use of ingredient lists as a source of information throughout product evaluations. While most consumers do not attend to ingredient information, this tendency can be slightly improved by prompting their consideration of naturalness. Future research should investigate the reasons for consumers' inattention to ingredient information and develop more effective strategies for conveying information to consumers. Highlights: Few consumers consider ingredient info. when evaluating food product naturalness. Choice-blindness paradigm shows low detection of changed ingredients on food label. Cues about naturalness considerations increases attention to ingredient information.